Reports and Indicators of Innovation in Chile - Pantoja, Alejandro (Base Diseño e Innovación, 2014)
The year of innovation is over and also a government which defined incentive actions and policies, which results and impact will be able to be evaluated later this year. However, we can describe the present context of innovation in Chile as from some related reports, figures, and indicators that allow us to foresee the scenario in which we are: what have been done well, what has to be done, and in a near future, contrast it with the initiatives pro innovation from the outgoing administration.